SwiShmem: Distributed Shared State Abstractions for Programmable Switches - Zeno, Lior; Ports, Dan R. K.; Nelson, Jacob; Silberstein, Mark (HotNets '20, 2020)
Programmable switches provide an appealing platform for running network functions (NFs), such as NATs, firewalls and DDoS detectors, entirely in data plane, at staggering multi-Tbps processing rates. However, to be used in real deployments with a complex multi-switch topology, one NF instance must be deployed on each switch, which together act as a single logical NF. This requirement poses significant challenges in particular for stateful NFs, due to the need to manage distributed shared NF state among the switches. While considered a solved problem in classical distributed systems, data-plane state sharing requires addressing several unique challenges: high data rate, limited switch memory, and packet loss.We present the design of SwiShmem, the first distributed shared state management layer for data-plane P4 programs, which facilitates the implementation of stateful distributed NFs on programmable switches. We first analyze the access patterns and consistency requirements of popular NFs that lend themselves for in-switch execution, and then discuss the design and implementation options while highlighting open research questions.